2010
DOI: 10.1002/jhm.675
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fragmentation of hospitalist care on length of stay

Abstract: Disclosure: Data collection, analysis, and author salaries were all paid for by IPC-The Hospitalist Company.BACKGROUND: Different hospitalist staffing models provide different levels of inpatient continuity of care, which may impact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 11 publications
2
64
1
3
Order By: Relevance
“…17 As noted, there was a trend towards a decreased LOS for patients initially cared for by the HMED team.…”
Section: Discussionmentioning
confidence: 91%
“…17 As noted, there was a trend towards a decreased LOS for patients initially cared for by the HMED team.…”
Section: Discussionmentioning
confidence: 91%
“…Epstein et al also reported that decreased continuity of care was associated with longer hospital length of stay. 6 Though provocative, the study is limited in that continuity and length of stay are interrelated. As a patient's length of stay increases, so does the likelihood of discontinuity.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of US hospital medicine practice, this fragmentation may compromise safety or throughput; however, no such deficit has been detected to date in the context of acute medicine practice in the UK. 13 Mismatch between AMU bed or staff capacity and the number or rate of hospital admissions can generate safety risks or give away efficiency gains. Further inefficiencies can develop if hospital-wide processes of handover, medical decision making, patient transport, and discharge are not synchronized with AMU outflow and intake.…”
Section: Weaknesses and Strengths Of Acute Medicine Model Applicable mentioning
confidence: 99%